Unemployed and alone? Unemployment and social participation in Europe. Issue 1 (9th March 2015) - Dieckhoff, Martina; Gash, Vanessa
Abstract : Purpose: – The purpose of this paper is to examine the relationship between unemployment and social participation and aim to identify the role of national policies and attitudes as possible mediators. Design/methodology/approach: – The authors use the 2006 EU-SILC module on social participation – a data set that provides rich information on social participation for 22/23 EU countries. They adopt a two-step multi-level design, allowing them to directly examine the impact of national policies and norms on individual outcome. Findings: – The paper reveals clear evidence that the unemployed have lower levels of social participation than the employed across a range of indicators. The paper also reveals that macro-level variables significantly affect the extent of these differentials in social participation. For instance, the authors found that societies that expose the unemployed to poverty risk have a larger social participation gap between the employed and the unemployed. Originality/value: – While the negative association between unemployment and social participation has been established in prior work, the study is the first one to employ a "large N" comparison and to use a multi-level design to statistically test the degree to which macro-level variables mediate the negative relationship between unemployment and social participation. The analyses were able to show that societal context can significantly alleviate the negative implications of unemployment for social participation.